Adult Education for Critical Consciousness: Luis Camnitzer and His Art as Critical Public Pedagogy - Ana Zorrilla (Adult Education Research Conference, 2014)
Luis Camnitzer’s work exemplifies connections between art and adult education for critical consciousness. Critical public pedagogy serves as this study’s theoretical framework. Textual analysis of his work and interviews with Camnitzer and others demonstrate his re-presentation of reality, involving audiences as meaning co-creators. Theory, research and practice implications are explored.